An Overview of Outsourcing in the Banking Industry - Singh, Jagjit (2005)
Outsourcing has gained precedence as an important strategic tool for management. Especially in banking, where banks have been outsourcing their IT operations for the past two decades, the concept of outsourcing entire business processes to third party service providers has been growing in popularity over the years.